212k views
1 vote
The steps below show the incomplete solution to find the value of x for the equation

5x − 2x − 3 = −2 + 17:

Step 1: 5x − 2x − 3 = −2 + 17
Step 2: 5x − 2x − 3 = 15
Step 3: 3x − 3 = 15

Which of these is most likely the next step?

2 Answers

3 votes

3x = 18

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

User Guven
by
6.3k points
7 votes
The next step is most likely to add 3 to both sides, so that 3 cancels out, and 15 turns into 18.

The answer is: Step 4: 3x = 18
(I don't know if you want me to continue or not, but I will) ;)

Then divide by 3 on both sides so that 3 cancels out and 18 turns into 6, and you have the value of x.

Step 5: x = 6

You can check your answer by replacing x with 6.

5 · 6 - 2 · 6 - 3 = -2 + 17
15 = 15

Hope this helped! If you have anymore questions or don't understand, please comment or DM me. :)
User Wrren
by
6.3k points